The Influence of halalan tayyiban on Muslim decent spiritual life and its relation to al-Ghazali’s concept of breaking the two desires - Ssuna, Salim (KIRKHS, IIUM, 2020)
The concept of halalan tayyiban is very central to a Muslim spiritual life, it has a direct influence on the true practice and fulfilling the religious obligations as demanded by the Almighty Allah. The centrality of this concept attracted and still attracts numerous studies, which cover a multiplicity of topics ranging from mainly branding to scientific technicalities involved in the production of permissible consumable products during modern times. This study will focus on the implication and influence of halalan tayyiban on Muslim decent spiritual life and how this relates to al-Ghazali’s concept of breaking the two desires. The study uses a descriptive analytical approach which is mainly interpretative in form of textual commentary. The study observed that a combination of these two concepts will lead to a more refined understanding of the concept of halalan tayyiban and its influence on one’s spiritual life.